2001
DOI: 10.1002/mrm.1283.abs
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow and energy metabolism on injury and Rb uptake in pig hearts: An 87Rb and 31P NMR study

Abstract: In this work the roles of coronary flow (CF) and metabolism in Rb ؉ (K ؉ congener) uptake were studied. In isolated pig hearts the left anterior descending artery (LAD) was cannulated to maintain adequate perfusion of the LAD bed. Rb ؉ loading was initiated and the LAD flow was either completely stopped (no flow (NF)) or reduced to 12% (low flow (LF)), or buffer was deoxygenated without change in flow (hypoxic flow (HYP)) for 2 h. CF through the LAD was then restored to normal, or perfusion was switched to oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…87 Rb MR spectroscopy (1–6) and imaging (7–10) were used to monitor K + transport and distribution in isolated hearts under normal and pathological conditions. Two important properties of rubidium ion were utilized in these studies.…”
mentioning
confidence: 99%
“…87 Rb MR spectroscopy (1–6) and imaging (7–10) were used to monitor K + transport and distribution in isolated hearts under normal and pathological conditions. Two important properties of rubidium ion were utilized in these studies.…”
mentioning
confidence: 99%
“…Indeed, we have recently shown that low flow ischemia and regional hypoxia result in a decrease in Rb image intensity in the affected area to 75-80%, which corresponds to reversibly damaged tissue. 10 …”
Section: Rb Distribution and Size Of The Area At Risk And Infarctmentioning
confidence: 97%
“…At the same time the infarction size was less than half of the area at risk ($40% of the maximum). [8][9][10] Note that in the in vivo pig model of cardiac infarction, periods of 120 min occlusion [20][21][22] or longer 23 resulted in formation of infarct areas of 50-95% of the area at risk upon reperfusion.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations